Pengaruh Latihan Kebugaran Jasmani terhadap Kemampuan Teknik Dasar Shooting Permainan Sepakbola Siswa Sekolah Menengah Pertama - Rifki Sabik; Ega Trisna Rahayu (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
Abstract This study aims to improve shooting ability by treating physical fitness tests. This study used an experimental method using a one-group pretest-posttest design. The research was conducted to practice shooting skills in soccer games. The research subjects were junior high school students with 16 students consisting of 6 boys and 10 girls with an average age of 15 years. The purposive sample was used as a data collection technique and analyzed using quantitative description and surgical test. The results show that the shooting ability of junior high school students has increased. There was an increase because physical fitness was able to stimulate students to be active in shooting soccer games. In conclusion, there is an effect of physical fitness training on the basic technical skills of shooting soccer games for junior high school students. Keywords: , Junior high school, Physical Fitness, Shooting